Nadranan Ritual: Cultural Values of the Agricultural and Fishermen Communities in Cirebon, West Java, Indonesia - Ma’mun, Titin Nurhayati (TAWARIKH, 2011)
ABSTRACT: âNadrananâ is a traditional ceremony celebrated every year by the society lived in Cirebon coastal area, West Java, Indonesia. The ceremony, taken usually two days three nights in the vicinity of the Sunan Gunung Jati cemetery region, is intended to show appreciation of the Cirebon society as many of them have jobs as farmer or sailor. In their development as culture phenomenon, the ânadrananâ ceremony experienced many significant changes on its practice and its perception. The most significant and subtle modification are the removal of the âLarung Sajenâ ritual. The removal is unusual since, in many places, âLarung Sajenâ is the main core of the âNadrananâ ceremony. The modification indicates that âNadrananâ in Cirebon coastal society is closer as a culture practice, which is accepted as a traditional heritage rather than as a ritual practice which often invites controversy. Finally, âNadrananâ is essentially a traditional ritual usually conducted by the fishermen community, although in Cirebon it is also held by the agricultural community. KEY WORDS: âNadrananâ, ceremony, ritual culture, agricultural society, and fishermen community.About the Author: Dr. Titin Nurhayati Maâmun is a Lecturer at the Arabic Literature & Language Departement, Faculty of Letters UNPAD (Padjadjaran University), Jalan Sumedang-Bandung Km.5, Jatinangor, Sumedang, West Java, Indonesia. She can be reached at: titin_makmun@yahoo.comHow to cite this article? Maâmun, Titin Nurhayati. (2011). âNadranan Ritual: Cultural Values of the Agricultural and Fishermen Communities in Cirebon, West Java, Indonesiaâ in TAWARIKH: International Journal for Historical Studies, Vol.2(2) April, pp.191-202. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (February 24, 2011); Revised (March 29, 2011); and Published (April 28, 2011).